1993
DOI: 10.1128/aac.37.4.825
|View full text |Cite
|
Sign up to set email alerts
|

Mercury released from dental "silver" fillings provokes an increase in mercury- and antibiotic-resistant bacteria in oral and intestinal floras of primates

Abstract: In a survey of 640 human subjects, a subgroup of 356 persons without recent exposure to antibiotics demonstrated that those with a high prevalence of Hg resistance in their intestinal floras were significantly more likely to also have resistance to two or more antibiotics. This observation led us to consider the possibility that mercury released from amalgam ("silver") dental restorations might be a selective agent for both mercuryand antibiotic-resistant bacteria in the oral and intestinal floras of primates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
135
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(146 citation statements)
references
References 32 publications
5
135
0
3
Order By: Relevance
“…The selective agent need not be even an antimicrobial used for treatment but may be another selective agent that favors a trait linked to drug resistance in commensals. For example, exposure of commensal gut flora to mercury during installation and removal of dental fillings selected for drug-resistant strains that were also mercury resistant (82). Genes conferring resistance to environmental hazards such as heavy metals are often transferred between lineages together with antibiotic resistance genes on plasmids (83).…”
Section: Explanations For the Proliferation Of Mdr Strainsmentioning
confidence: 99%
“…The selective agent need not be even an antimicrobial used for treatment but may be another selective agent that favors a trait linked to drug resistance in commensals. For example, exposure of commensal gut flora to mercury during installation and removal of dental fillings selected for drug-resistant strains that were also mercury resistant (82). Genes conferring resistance to environmental hazards such as heavy metals are often transferred between lineages together with antibiotic resistance genes on plasmids (83).…”
Section: Explanations For the Proliferation Of Mdr Strainsmentioning
confidence: 99%
“…It was observed that bacteria in the oral cavity developed a mercury resistance which is transferred on the same plasmids as some antibiotic-resistances. Therefore, it was postulated that continuous mercury exposure might cause a continuous selection pressure toward an antibiotic-resistant state [145]. Mouth flora of some children also contain bacteria resistant to mercury and to antibiotics [146].…”
Section: Development Of Resistancementioning
confidence: 99%
“…(Whether those not genetically susceptible could also be directly toxically affected by mercury is unknown; many widely divergent opinions and research reports have been published over the last few decades (247,248,(251)(252)(253)(254)(255)(256). Recent reports connect amalgams with oral cavity ill-health (248,257), increase in antibioticresistant bacteria in oral and intestinal cavities (258), multiple sclerosis (259,260), psychological complaints such as depression, excessive anger, and anxiety (261), and cardiovascular symptoms such as fatigue and high blood pressure (262).…”
Section: Individual Ids Descriptionsmentioning
confidence: 99%